Pandangan Mahasiswa Universitas Negeri Surabaya terhadap Budaya Patriarki di Era 5.0 - Azizah, Erliyana Freida Nur; Hanani, Azrina Khalwa; Sofiana, Sofiana; Puspitahaqni, Vivi; Berliana, Aulia Risa (Lembaga Yasin AlSys, 2024)
The rise of patriarchal culture in the 5.0 era is still a topic of conversation and debate among society. The observed patriarchal culture is still a hot topic of discussion because its dominance in society influences various aspects of life, such as gender inequality. Men have power in society, while women have a small percentage of influence. The method used for this research is a quantitative method which is defined as research in the form of numbers processed through scoring. Quantitative research was processed and analyzed using statistical calculation techniques with 277 respondents collected. And from the analysis carried out by researchers, Surabaya State University students disagree regarding patriarchy which is still a strong culture among society in the 5.0 era.